Promoting Sustainability through Indonesian Community and Faith-Based Perspectives: Insights from the Semesta Documentary Film Screening - Pangesti, Ayendha Kukuh; Nuryaman; Pangesti, Kartika Puji; Hariyanto; Nigel, Gabriel (Abdi Geomedisains, 2025)
This community engagement program aims to enhance public awareness and understanding of how cultural and spiritual values contribute to environmental action. The primary issue addressed is the marginalisation of religious, faith-based, and cultural perspectives within dominant environmental discourses, despite their long-standing role in shaping sustainable practices across communities. The program, titled “Sound of Semesta,” was conducted at the University of Sydney using a documentary screening of Semesta: Island of Faith, followed by a panel discussion. The implementation adopted the Planning, Organizing, Actuating, and Controlling (POAC) management framework to ensure effective delivery. The findings indicate that cultural and spiritual narratives significantly strengthen ecological awareness and encourage critical reflection on sustainability rooted in Indigenous and faith-based practices. Panel discussions highlighted that spiritual concepts, such as stewardship, adat law, and the sacredness of nature, serve as ethical drivers for collective environmental responsibility. The program also revealed that while local wisdom is essential, sustainable environmental practices require systemic support, including policy alignment, education, and cross-sector collaboration, to withstand external pressures. Overall, this initiative demonstrates that integrating cultural heritage and spiritual values into environmental education offers a meaningful and inclusive pathway for addressing contemporary ecological challenges and advancing sustainable development discourse. Future events may consider screening the documentary in full or presenting it in thematic segments across multiple sessions, complemented by post-screening discussions and short reflective essays submitted by participants to deepen critical engagement.